CAUSE AND EFFECT IN PROMOTING A PROJECT - SEVERIAN-VLĂDUȚ IACOB (Annals of the University of Petrosani: Economics)
For a project to be considered successful it is necessary, besides a proper coordination, to be also done a good and wide promotion. In view of communication, promotion and maintenance ensures the organization's image. Disturbances occurring in any type of project, as a result of poor promotion, affect the image of the team and highlight the weaknesses in its management. Therefore, the promotion should be permanently monitored and evaluated. Cause-effect analysis is one of the ways we can identify some of nonconformities of the promotion process within a project.